This action might not be possible to undo. Are you sure you want to continue?

# e as the limit of (1 + 1/n)n

**Math 122 Calculus III D Joyce, Clark University Sept 2011
**

1 This is a small note to show that the number e The ﬁrst integral equals n+1 , the second equals 1 1 is equal to a limit, speciﬁcally ln(1 + n ), and the third equals n . Therefore, n→∞

lim 1 +

1 n n

= e.

1 n+1

≤ ln 1 +

1 n

1 ≤ n.

Sometimes this is taken to be the deﬁnition of e, but Exponentiating, we ﬁnd that I’ll take e to be the base of the natural logarithms. 1 1 1 e n+1 ≤ 1 + n ≤ e n . For a positive number x the natural logarithm of x is deﬁned as the integral Taking the (n + 1)st power of the left inequality x gives us 1 dt. ln x = 1 n+1 e≤ 1+ n 1 t th Then e is the unique number such that ln e = 1, while taking the n power of the right inequality gives us that is, 1 n e 1 + n ≤ e. 1 dt. 1= Together, they give us these important bounds on 1 t The natural exponential function ex is the function the value of e: inverse to ln x, and all the usual properties of loga1 n+1 1 n . 1+ n ≤e≤ 1+ n rithms and exponential functions follow. n 1 Here’s a synthetic proof that e = lim 1 + n . Divide the right inequality by 1 + 1 to get n→∞ n A synthetic proof is one that begins with statee 1 n ments that are already proved and progresses one 1 ≤ 1+ n 1+ n step at a time until the goal is achieved. A defect of synthetic proofs is that they don’t explain why which we combine with the left inequality to get any step is made. e 1 n ≤ e. 1 1 ≤ 1+ n Proof. Let t be any number in an interval [1, 1 + n ]. 1+ n Then e 1 1 But both ≤ 1. 1 → e and e → e, so by the pinching 1 ≤ 1+ n t 1+ n theorem Therefore 1 n 1 + n → e, 1 1 1 1+ n 1+ n 1+ n 1 1 also. q.e.d. dt ≤ 1 dt. 1 dt ≤ t 1+ n 1 1 1 1